COMPARATIVE PRODUCTION PROGRAMS AND IMPROVE QUALITY OF AGRICULTURES AND AGRARIAN PRODUCTS - Simić, Jeremija; Bošković, Jelena; Hojka, Zdravko; Vukosav, Marija; Sarić, Radmila (Economics of Agriculture, 2006)
This paper realizes and defines comparative programs of agriculture production. For this, purpose previous pointed on diversity and comparatively available natural resources (climate, soil, water biodiversity of flora and fauna). Also realizes technical-technological accomplishments and possibilities to adjust sustainable development of agriculture and agrarian sector. In according with available structure and quality of agro ecological conditions, market demands, in this paper was define comparative and developing programs of agriculture production and agrarian manufactured products. Comparative programs of these products, defined according to agriculture organic production and possibilities of production biological quality organic products for advance realizes segment of market. In frame of quality developing of agrarian products, pointed on politics and modalities of apply international standards in function of process managing and quality of products, manufacture and market exchange of agrarian products. For these purpose, pointed on specificity of creating, certificating and marking of agrarian products.